2006
DOI: 10.1007/s00268-005-0463-5
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating Cardiac Injuries: Recent Experience in South Africa

Abstract: A high index of suspicion for penetrating cardiac injury and an understanding of the modes of presentation can lead to rapid diagnosis even by inexperienced junior staff. Such a structured approach to patients with penetrating trauma to the chest leads to early definitive management and acceptable results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
89
0
16

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(110 citation statements)
references
References 34 publications
5
89
0
16
Order By: Relevance
“…In agreement with others, our results have shown that victims of penetrating cardiac injuries are predominantly young males [1,3,14,16,20,24,25,30].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In agreement with others, our results have shown that victims of penetrating cardiac injuries are predominantly young males [1,3,14,16,20,24,25,30].…”
Section: Discussionsupporting
confidence: 93%
“…According to Degiannis et al data, 46% of patients with a single stab wound had it in the precordium. The mortality rate among patients with precordium stab wounds was 4%, whereas among persons with non-precordium stab wounds it was 25%, with a statistically significant difference (p = 0.03) [14]. Navsaria et al [15] reported that a stab wound in the precordium resulted in heart injury in 60% of cases (in our study -71.5%); Penetrating cardiac injuries: 28-year data analysis on the other hand, 85% of the heart-injured persons had a wound in the precordium area (in our data -81.2%).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations